Social Jetlag Is Associated With Impaired Metabolic Control During a 1-Year Follow-Up - Mota, Maria Carliana; Silva, Catarina Mendes; Balieiro, Laura Cristina Tibiletti; Fahmy, Walid Makin; Marqueze, Elaine Cristina; Moreno, Claudia Roberta de Castro; Crispim, Cibele Aparecida (Frontiers in Physiology, 2021)
Previous studies have identified social jetlag (SJL) as a risk factor for non-communicable chronic diseases (NCCDs), but its association with metabolic control over time is unclear in the literature. Therefore, we examined the influence of SJL on metabolic parameters and blood pressure (BP) in patients with NCCDs over a 1-year follow-up. This retrospective, longitudinal study included 625 individuals (age: 56.0 + 12.0 years; 76% female) with NCCDs (type 2 diabetes mellitus [TD2], systemic arterial hypertension [SHA], obesity, or dyslipidemia). SJL was calculated based on the absolute difference between mid-sleep time on weekends and weekdays. Current metabolic parameters and BP of the patients were compared with data from a year prior. Generalized estimating equations (GEE) and multiple linear regression analyses were used to examine the association among SJL, metabolic parameters, and BP. Multiple linear regression analyses adjusted for confounders showed that SJL was positively associated with the delta difference of fasting glucose (β=0.11, p=0.02) and triglyceride levels (β=0.09, p=0.04) among all subjects with NCCDs, and with fasting glucose (β=0.30, p=0.0001) and triglyceride levels (β=0.22, p=0.01) in the TD2 group. GEE analysis demonstrated an isolated effect of SJL on diastolic BP . High SJL impaired clinical and metabolic control in individuals with NCCDs, leading to a worse profile after a 1-year follow-up, particularly among type II diabetics.